2015
DOI: 10.7150/jca.11420
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CUEDC2 Predicts Poor Prognosis in Ovarian Serous Carcinomas

Abstract: CUEDC2, a newly reported protein, plays critical roles in many biological processes, such as cell cycle, inflammation and tumorigenesis, however, its expression in ovarian serious carcinoma is still poorly understood. In this study, we performed an immunohistochemical study on 101 cases of ovarian serous carcinoma tissues to investigate whether CUEDC2 is a useful biomarker to evaluate the progression of ovarian serous carcinomas. The data showed that the overexpression of CUEDC2 was observed in 59.4% of ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…In our study, A-catenin staining was predominantly found in the cytoplasm or in the cytoplasm and membrane in both LGSOC and HGSOC. Lee et al 16 reported that nuclear expression of A-catenin was associated with high-grade tumors and worse median survival; no association was found between membrane or cytoplasmic staining and histological 14 reported that A-catenin expression was not different between LGSOC and HGSOC. However, they concluded that overexpression was associated with advanced stages and poor OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, A-catenin staining was predominantly found in the cytoplasm or in the cytoplasm and membrane in both LGSOC and HGSOC. Lee et al 16 reported that nuclear expression of A-catenin was associated with high-grade tumors and worse median survival; no association was found between membrane or cytoplasmic staining and histological 14 reported that A-catenin expression was not different between LGSOC and HGSOC. However, they concluded that overexpression was associated with advanced stages and poor OS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, A-catenin expression was not associated with stage, histological grade, platinum chemotherapy, or OS in LGSOCs or HGSOCs. 14 The strength of this study is that it is the first investigation that correlated the IHC expression of BRCA1, Ki67, and A-catenin in response to platinum-based chemotherapy and prognosis in a selected sample of Brazilian woman with serous OCs. The main limitations of this study are its retrospective nature and immunohistochemical technique based on TMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, recently more attention has been focused on the molecular markers of the P13K/AKT pathway and WNT /β-catenin pathway, which are being widely studied in ovarian carcinoma. 18,19 In this scenario, an institutional based cross-sectional observational study was done among the different types of ovarian carcinoma cases with a purpose to assess the β-catenin and PTEN expression and study their correlation with histological grade and stage of ovarian carcinoma by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The H&E-stained slides of the different biopsies were reviewed by two experienced pathologists and one appropriate paraffin block was selected for this study. Histopathological grading was performed using the World Health Organization (Pathology and Genetics Tumors of Gynecological System) criteria (with 72 low-grade tumors and 110 high-grade tumors) (19 (19). None of the ovarian carcinoma patients received pre-operative radiation or chemotherapy prior to surgery.…”
Section: Methodsmentioning
confidence: 99%